(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2018)
Estimation of stature holds a special mention in the field of forensic medicine and forensic anthropology, Among the various parameters of identification, In our institute estimation of stature has obvious utility in identification process as there are number of cases are reported every year where identity remains unknown. This study will be conducted to find out possible correlation between stature of an individual and combined length of forearm and hand and derive regression formula to estimate the stature from anthropometry of combined length of forearm and hand. This cross sectional study was carried out on 250 deceased males of age 21 years and above brought for post mortem examination in mortuary of Forensic Medicine Department, M.G.M. Medical College and M.Y. Hospital, Indore (MP).The mean combined length of right and left forearm and hand in males was 45.87 ± 2.31 and 45.90 ± 2.31 respectively, whereas mean stature was found to be 163.82 ± 5.42 cm in males. In this study maximum stature in males was found to be 179.5 cm, while minimum stature was found to be 153.6 cm. It can be concluded that this study has provided regression equations for parameters that can be used for stature estimation in the population of Indore. These equations should not be used for other Indian population groups. Definite proportion exists between the stature and combined length of forearm and hand in all individuals